(untitled) (Global Journal of Medical Research, 2023)
Goal Recognize the relevance of hospitalizations for musculoskeletal injuries due to accidents at work in Brazil Methods It is a retrospective epidemiological study qualitative quantitative with secondary data analysis and cross-sectional typology in the public databases of the Ministry of Labor and Social Security delivered by the Federal Government Descriptors in health sciences musculoskeletal injuries accident at work injuries due to accidents at work workers absenteeism Results In Brazil during 2015 to 2020 there is evidence of a high number of accidents at work resulting in 65 9 of musculoskeletal injuries The most affected age was between 30-39 years the male gender corresponded to 63 3 of the cases upper limb injuries were the most prevalent and 36 1 billion were spent in aids